Resistivity and AE Response Characteristics in the Failure Process of CGB under Uniaxial Loading - Tingye Qi; Guorui Feng (Advances in Materials Science and Engineering)
To understand the characteristics of the acoustic emission (AE) and electrical resistivity of cemented coal gangue backfill (CGB) under uniaxial compression, the variations in these characteristics at 1 day, 3 days, and 7 days are analyzed by means of a stress-strain-resistivity-AE test, and the microperformances are investigated. The research results indicate that the AE can reflect the initiation and propagation of cracks and later explain the variation of the resistivity of the specimens under the uniaxial loading. The cumulative energy curve of AE is approximately two straight lines corresponding to the peak stress, and the difference in the linear slope gradually decreased with the increasing curing time due to the lower pore solution content and the compact pore structure. The relationships between the stress and resistivity and the loading condition before and after the peak stress at different curing times were established. Therefore, it is of great significance to predict the stability of the filling body by monitoring the AE and resistivity variations of the filling body. In addition, it is possible to calculate the roof stress using the relation equation between the resistivity and stress.